The influence of Altitude on the Species Composition of Diving Beetles (Coleoptera; Adephaga; Dytiscidae) of Eastern and South Eastern Region of Turkey - Aykut, Medeni; Tuğal, İhsan (My University, 2023)
This study was carried out between 2013 and 2019 in five provinces located in Eastern and South Eastern Anatolian Region of Turkey. The dytiscid specimens were collected from a total of 226 sampling sites that altitudes varied between 500 and 2,700 meters. The 226 sampling sites were classified into one of six altitudinal levels defined by semi open intervals with amplitude of 300 m. A total of 45 species belonging to the family Dytiscidae were identified. A detailed ecological analysis related to altitude is made by means of the distribution of 45 identified species. The richness of species was analyzed at different altitudinal levels. The indicator species were determined by establishing their altitude profile in terms of reciprocal species-factor information. The species density is highest in altitudinal level 2 (800-1100m) and is gradually decrease by increasing of altitudinal level. Ten representative species are placed into three groups: species occurring at high altitude; species present at low altitude and species occurring along the entire altitudinal gradient.